Morphometric Identification of Entry Points Of Pedicle Screw Fixation in C1 Vertebra - Sharma, Krishna (Annapurna Journal of Health Sciences, 2025)
Introduction: There is great concern during surgery in the CV junction region of fear of injury to the closely related neurovascular structures. Surgery in the region includes decompression, reduction of subluxation and stabilization by internal fixation. Internal fixation is commonly done by placement of screws and rods which gives an immediate and long term rigid and strong fixation. The dissection in the region, is well realised to be difficult and associated with neurovascular issues, particularly when finding the entry point for screw fixation in atlas. Methods: A prospective study was conducted for anatomic study of C1 osteology to locate the C1 screw entry point and where data was used in patients requiring C1 screw fixation. In this study, morphometric data were obtained from the C1 screw insertion entry points on the posterior arch of C1, in reference to the screw entry point of C2 in 3D CT images of normal persons, sawdust models, and cadavers. Using this information, entry points for pedicle screw fixation were located in C1 posterior arch in 18 patients needing C1-C2 fixation. Results: It was found that the entry point of screw in the posterior arch of the C1 vertebra was 4 mm ±3 mm lateral to the vertical line drawn from the pedicle screw entry point at the C2 vertebra. Additionally, the entry points was 22 ± 3 mm from the posterior tubercle of posterior arch. Also, to identify the pedicle screw insertion points, similar measurements were obtained from CT scans of 18 patients requiring C1-C2 fixation. Conclusion: By using morphometric analysis, the entry point for pedicle screw fixation of C1 can be easily located on the posterior arch of atlas, thereby reducing the need for extensive dissection and the potential for injury to the neurovascular structures.